Biotic and abiotic drivers of barnacle recruitment along a sub-Arctic intertidal rocky shore - Prieto Del Campo, Marta (UiT Norges arktiske universitet, 2023)
Most marine ecological research in the Arctic has focused on open water ecosystems, while coastal ecosystems are systematically under-studied. However, Arctic near-shore ecosystems are highly stressed environments and play a major role in biogeochemical cycling (e.g., nutrient input from thawing permafrost). Furthermore, the Arctic region has extreme environmental conditions which are expected to be stronger modified by climate change than most other regions on earth. Ecological models state connections between environmental stress and the relative importance of species interaction regulating ecological communities. Many studies testing environmental stress models have been conducted on rocky intertidal shores of the temperate zones, which are commonly inhabited by sessile invertebrates, such as mussels and barnacles, slow moving predators, such as dogwhelks and limpets, and canopy-forming macroalgae. These studies showed, for instance, that barnacle (Semibalanus balanoides) settlement and recruitment are negatively affected by seaweed canopy whiplash and limpet bulldozing and also vary over small spatial scale with shore height due to strong desiccation gradients. However, canopies can also benefit both limpets and barnacles, providing a microclimate with reduced desiccation effects. The empirical evidence of those studies from temperate regions, may, however, not be applicable to the Arctic intertidal. This study focusses on the limpet-seaweed-barnacle interactions in the Arctic intertidal zone, as a highly stressful environment for which information on species interactions is extremely limited. Here, I report on: (1) the effect of shore height on barnacle (S. balanoides) settlement success and recruit density in relation to the effect of seaweed (Ascophyllum nodosum) canopy presence and (2) the separate and combined effects of the presence of seaweed (A. nodosum) canopy and, limpets (Patella vulgata), on the density of barnacle cyprids, recruits and adults. This experimental study was performed along the ...